2023
DOI: 10.4103/sjg.sjg_35_23
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological characteristics of early-onset colorectal cancer in South Korea

Abstract: Background: Early-onset colorectal cancer (EOCRC) may differ by race and ethnicity, and recently South Korea has witnessed a surge in cases. We aimed to evaluate the clinical and pathological features of patients with EOCRC, and to determine the predictors of overall survival. Methods: In this retrospective study, EOCRC was defined as CRC diagnosed in patients aged < 50 years, and late-onset CRC was defined as CRC diagnosed in those over 75 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…survival time and quality of life of patients with advanced metastatic disease have been improved [27] .However, it has been shown that while improving the prognosis of patients with CRC, chemotherapeutic agents also increase the rate of associated complications [26,15] . Chemotherapy primarily induces excessive immune activation and can even directly harm non-target organs, especially the heart, with cardiovascular causes being the most common non-tumor death reasons in colorectal cancer [44] .…”
Section: Discussionmentioning
confidence: 99%
“…survival time and quality of life of patients with advanced metastatic disease have been improved [27] .However, it has been shown that while improving the prognosis of patients with CRC, chemotherapeutic agents also increase the rate of associated complications [26,15] . Chemotherapy primarily induces excessive immune activation and can even directly harm non-target organs, especially the heart, with cardiovascular causes being the most common non-tumor death reasons in colorectal cancer [44] .…”
Section: Discussionmentioning
confidence: 99%